ETHICS OF VACCINATION IN CHILDHOOD - Meta Rus; Urh Grošelj (The Society for Children with Metabolic Disorders, 2021)
In countries with well-established immunisation programmes, vaccination is the 'victim of its own success', because the low incidence of diseases prevented by vaccines has diminished the experience of their historical burdens and hence the obvious beneﬁt of vaccination. The increasing number of parents who reject vaccination of their children already threatens or even effectively disables herd immunity level of the population and results in outbreaks of previously already controlled infectious diseases. We aimed to design a framework for ethical analysis of vaccination in childhood based on the four principles of biomedical ethics (respect for autonomy, non-maleﬁcence, beneﬁcence and justice) to provide a comprehensive and applicable model for addressing the ethical aspects of vaccination at both the individual and societal levels. The principle-based framework can be especially useful to paediatricians in primary care when looking for the best approach to the treatment of children of vaccine-hesitant parents. We suggest ﬁnding an 'ethical equilibrium', which means that the degree of respect for parents' autonomy is not constant, but variable; it depends on the level of established herd immunity and it is speciﬁc for every society. When the moral obligation of individuals to contribute to herd immunity is not fulﬁlled, mandatory vaccination policies are ethically justiﬁed, because states bear the responsibility to protect herd immunity as a common good.